THE EFFECT OF MONTH DAY ON THE CATCH OF KELONG BILIS IN MALANG RAPAT VILLAGE GUNUNG KIJANG DISTRICT BINTAN REGENCY RIAU ISLAND PROVINCE - Meri Yosephin Sihotang; Bustari Bustari; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractThis research was conducted out in April 2018 in Malang Rapat Village of Gunung Kijang District, Bintan Regency, Riau Islands Province. The purpose of this study was to determine the effect of moon days on diversity, composition and differences in the catch of kelong bilis. The method used is a survey method and sampling method to calculate the catch. This study was conducted eight days, namely four days of bright months and four days of dark months.The catches of kelong bilis are anchovy, squid, tamban fish. The total catch in the bright moon was 43.4 kg (6480 individuals tails) and the catch in the dark moon was 160.3 kg (202806 individuals tails). The weight composition of the catch in bright months is anchovy 2.5 kg (6%), squid 31.6 kg (73%), tamban fish 9.3 kg (21%). And in the dark month, it was anchovy 82.5 kg (52%), squid 58.4 kg (36%), tamban fish 19.4 (12%). The diversity weight of the kg that has been calculated from both months is 68% and 28%. From the calculation of the t-test, there is a significant difference in the catch of kelong bilis on the month day. Kata Kunci: Kelong Bilis, Month Day, Composition, Diversity